(untitled) (Acta Polytechnica CTU Proceedings, 2018)
Solid state physics is a basic natural science focused on understanding connections between structure of the condensed matter and its properties. The main disciplines of the present solid state physics cover experimental research of the microscopic structure of the condensed matter (from crystalline matter, macromolecular and biological substances to mesomorphous and amorhous materials), spectroscopic and optical characterisation of physical and chemical properties of solid matter and complex functional super-structures or research of functional multi-ferroic materials. The achievements of solid state physics find great application in interdisciplinary fields covered under the title material engineering. An inseparable instrument of the new materials research is computer simulation of structure and properties of the condensed matter. As a related field, also the physics of materials was represented among the presenters this year. This covers materials diagnostics, investigation of the material fatigue, continuum dynamics, radiation damage of materials, or acoustic properties of materials – science domains which play an inseparable role in testing and development of new materials. The aim of the conference was to provide the students the opportunity to present their results before broader audience, develop their presentation skills and discus the scientific topics with other experts. Scientific and Organizing Comittee: Ladislav Kalvoda Petr Sedlák Martin Dráb Tomáš Koubský Kateřina Dragounová Jiří Čapek Petr Levinský Jaroslava Fojtíková Guarantor of the peer review process: Tomáš Koubský Guarantor of language editing: Tomáš Koubský Guest Editor: Tomáš Koubský